Use of ultrasonic spectroscopy and viscosimetry for the characterization of chicken skin collagen in comparison with collagens from other animal tissues - Gojkovic, Zivan; Marova, Ivana; Matouskova, Petra; Obruca, Stanislav; Miloslav, Pekar (Preparative biochemistry & biotechnology, 2014)
Use of traditional sources of collagen such as pork, bovine, and carp has some limitations. Chicken skin can be valuable alternative. In this work collagen was isolated from chicken skin using a modified procedure. Molecular properties of chicken collagen were analyzed and compared to collagen from other animal skins. Acid-soluble collagen type I was obtained with a yield of 25% and water content around 67%. Viscosimetry and ultrasonic spectroscopy were newly used for molecular characterization. By ultrasonic attenuation measurements, a pre-aggregation phase in the interval from 20°C to 27°C was observed, which is a proof of disaggregation and liquefaction. From 40°C upward, the liquefaction process finishes and aggregation continues. In a bovine sample this phenomenon starts at 40°C, in chicken at 50°C, and continues until 70°C. By viscosimetry, the denaturation temperature was confirmed as 40°C for bovine and 50°C for chicken collagen. Chicken collagen has a two times higher lysine level than bovine, which provides molecular stability side-chain interactions. With regard to higher thermal stability and favorable amino acid composition, waste chicken skin has the potential to be an excellent alternative source of raw collagen with applications in the food industry and biomedicine.
Keywords: denaturace proteinů; vysoká teplota; Protein Stability; Protein Aggregates; spektrální analýza; Spectrum Analysis; kur domácí; Collagen; kolagen; Amino Acids; kůže; ultrazvuk; prasata; Chickens; Ultrasonics; Animals; aminokyseliny; Hot Temperature; zvířata; Cattle; skot; Viscosity; viskozita; Swine; stabilita proteinů; elektroforéza v polyakrylamidovém gelu; proteinové agregáty; Protein Denaturation; Electrophoresis, Polyacrylamide Gel; Skin